The Conceptology of bid’ah: Imam Ahmad’s Perspective and Its Application in the Contemporary Era - Adynata, Adynata; Rahman, Syahrul; Darussamin, Zikri (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2022)
The term bid'ah has been hotly discussed in recent years. The diversity of views of scholars and the diversity of definitions are hot issues to be studied. Few are antipathy to this study, which sometimes leads to friction and disputes in the Muslim community. Imam Ahmad has a unique concept and is considered firm in determining the heresy of one case. This article focuses on examining the concept of Imam Ahmad's bid'ah and applying it to solving contemporary problems. Many expressions of sunnah, sunnah clerics (ulama), sunnah mosques, and sunnah studies have been expressed in recent years. Two good words sometimes create discomfort in the community and leave an impression. Others not labeled as sunnah are not part of the sunnah. This literature research uses the method of textual criticism of classical references that contain Ahmad's views. Globally there are two findings in this article; First, heresy, according to Imam Ahmad, only produces two taklify laws, namely haram or makhruh. Second, cleric, mosque, and sunnah studies can also be categorized as bid'ah, which is judged makruh.